Molecular Docking Aided Study of Transient Metal Inclusion and Tertiary Complexation of Fenofibrate: Effect on Solubility - Panda, Pratikeswar; Sahoo, Soumya Ranjan; Rout, Sudhansu Sekhar; Mohapatra, Rajaram (Drug Delivery Letters, 2025)
BackgroundFenofibrate, a widely used lipid-lowering agent, exhibits limited bioavailability due to its BCS Class II status and poor aqueous solubility. Enhancing its solubility is crucial to improving therapeutic efficacy.MethodsThis study explored solubility enhancement via molecular docking-guided screening of transition metal complexes and inclusion complexes with beta-cyclodextrin (β-CD). Transition complexes of fenofibrate with copper acetate were synthesized at a 1:1 molar ratio in a methanol-water mixture (2:1). Additionally, inclusion complexes of these metal complexes with β-CD were prepared in a 1:1 molar ratio and dried. Physicochemical characterization was performed using FTIR, XRD, and SEM analyses. Molecular docking identified potential interactions and conformational stability of the complexes.ResultsThe aqueous solubility of fenofibrate increased significantly, 17-fold in the transition metal complex and 25-fold in the β-CD inclusion complex compared to the pure drug. The complexes demonstrated structural changes, including amorphization, which likely contributed to enhanced solubility. Molecular docking revealed strong interactions between fenofibrate, copper acetate, and β-CD, supporting the formation of stable complexes.ConclusionThe results indicate that fenofibrate’s solubility can be markedly enhanced through complexation with transition metals and β-CD. These approaches, particularly the β-CD inclusion complexes, hold the potential for improving fenofibrate's bioavailability and therapeutic outcomes, offering a promising strategy for addressing solubility challenges in poorly water-soluble drugs.
Keywords: beta-cyclodextrin